PELAKSANAAN PEMBELAJARAN PROGRAM PENDIDIKAN KESETARAAN PAKET B BERBASIS LIFE SKILLS DI PKBM UMMATAN WASATHON (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Equivalency education through non-formal pathways plays a crucial role in providing learning opportunities for communities with limited access to formal education, particularly in preparing life skills to face the challenges of a dynamic workforce. This research aims to describe the implementation model of life skills-based learning in the Package B program at the Ummatan Wasathon Community Learning Center (PKBM), Kasemen District, Serang City, Banten Province, and identify supporting and inhibiting factors. The implementation method used a descriptive qualitative approach with data collection through observation and interviews. The results showed that life skills-based learning is implemented through planning stages (learning style analysis and material design), implementation (practical activities such as group discussions, presentations, and ice cream craft practice in English, Indonesian, and Craft subjects), and evaluation (assessment of material understanding and product quality). The program successfully enhanced creativity, collaboration, confidence, and motivation among learners, despite challenges such as age heterogeneity, resource limitations, and attendance consistency. The conclusion affirms that this approach is effective in equipping practical skills for personal and economic independence, with potential replication in other institutions. Research recommendations include intensifying fundraising for practical tools and developing blended learning modules.